Sosialisasi Kualitas Air Kota Sorong Sebagai Upaya Warning Sumber Daya Air Untuk Masa Depan - Alan C. Seme; Nurbia Nurbia; Azwar Rahmatullah; Anif Farida (CV. Multi Kreasi Media, 2024)
The aim of this service is to analyze the water quality of Sorong City, as well as disseminate information to the younger generation, namely high school students. The service stage is divided into two stages: observation and socialization. In the observation stage, measurements were carried out with the parameters measured being pH, conductivity, turbidity, TSS, TDS, and salinitas which were then compared with the standard criteria for river water quality according to Government Regulation No. 22 of 2021 concerning Implementation of Environmental Protection and Management. The analysis results show that it is still within safe limits, but the TSS and salinity values ​​are quite high, requiring management and control measures to maintain dam water quality. It is hoped that socialization will ensure that high school students can protect, conserve and maintain available water resources for the future.